Propagation of dispersive wave solutions for (3+1)-dimensional nonlinear modified Zakharov-Kuznetsov equation in plasma physics - Ali, Karmina K.; Seadawy, Aly R.; Yokus, Asif; Yilmazer, Resat; Bulut, Hasan (World Scientific Publ Co Pte Ltd, 2020)
In the current study, we instigate the four-dimensional nonlinear modified Zakharov-Kuznetsov (NLmZK) equation. The NLmZK equation guides the attitude of weakly nonlinear ion-acoustic waves in a plasma comprising cold ions and hot isothermal electrons in the presence of a uniform magnetic field. Two different methods are used, namely the sine-Gordon expansion method (SGEM) and the (1/G')-expansion method to the proposed model. We have successfully constructed some topological, non-topological, and wave solutions. In addition, the 2D, 3D, and contour graphs of the solutions are also plotted under the choice of appropriate values of the parameters.
Keywords: Four-dimensional NLmZK equation; SGEM; (1/G ')-expansion method; exact solutions